An Appraisal of Non-Formal Educated Mothers’ Perception on the Use of Birth Control in Kura Local Government, Nigeria - Wan, Suleman Ahmed; Umar, Muttaka; Umar , Isah; Idris, Rabi Tijjani (Kashere Journal of Politics and International Relations, 2025)
The study is set to appraise non-formal educated mothers’ perception on the use of birth control in Kura Local Government of Kano State. A sample of 130 reproductive-age women (15-39 years) in Kura LGA was drawn to respond to a questionnaire and In-depth Interviews (IDI). Health Belief Model was used for the study. The findings of the study revealed that culture frown on birth control, and tradition does not permit the use of contraceptives, because grandparents did not practice it. The nature of methods can be varied depending upon the interest, economic condition, side effects of the birth control methods. Also, the findings of the study revealed that their source of information about birth control methods was mostly friends, indicating influence of friends and peer group on birth control. The study recommended that empowering non-formal educated mothers with accurate information and resources on birth control can contribute to promoting family planning, and improving overall maternal and child health outcomes. Also, providing education, counseling, and access to a variety of contraceptive options can help empower women to make informed choices about family planning and reproductive health. Community-based programs, peer education, and outreach initiatives can also play a key role in addressing the attitudes of non-formal educated mothers with limited education towards birth control methods.